THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, AND COMPANY SIZE ON FIRM VALUE - Fadhilah, Umi Nurul; Khatik, Nur; Sinarasri, Andwiani (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This study aims to examine Capital Structure, Profitability, and Company Size in influencing Firm Value in the primary consumer goods sector, especially in the food and beverage sector. This research focuses on companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. The sample was taken purposively, using a quantitative data approach, and involved a total of 75 firmyears. Data were analyzed using multiple linear regression models with the help of IBM SPSS 26 software for Windows and Microsoft Office Excel. The results obtained show that Capital Structure has a negative effect on Firm Value, Profitability has a positive effect, and Company Size does not show a significant influence on Firm Value.